THE INFLUENCE OF SELF-SERVICE TECHNOLOGY AND CUSTOMER RELATIONSHIP MARKETING ON BANK MUAMALAT MALANG CUSTOMER LOYALTY WITH CUSTOMER SATISFACTION AS A MEDIATING VARIABLE - Aisyah Rokhma; Ronny Malavia Mardani; Ridwan Basalamah (RADJA PUBLIKA, 2025)
This study examines the influence of self-service technology and customer relationship marketing on customer loyalty at Bank Muamalat Malang, with customer satisfaction serving as a mediating variable. Using a quantitative research, this research analyzes data from 100 respondents collected through structured questionnaires. The study employs Structural Equation Modeling (SEM) to test the hypothesized relationships between variables. Results indicate that both self-service technology and customer relationship marketing significantly influence customer loyalty, with customer satisfaction playing a crucial mediating role. Self-service technology demonstrates a positive impact on customer satisfaction through ease of use, utility, time efficiency, and self-control dimensions. Customer relationship marketing, measured through trust, competence, commitment, communication, and conflict handling, also shows significant positive effects on customer satisfaction and loyalty. The mediation analysis reveals that customer satisfaction partially mediates the relationship between independent variables and customer loyalty. These findings provide valuable insights for Islamic banking institutions in developing effective strategies to enhance customer retention and loyalty through technological innovation and relationship management. Keywords: self-service technology, customer relationship marketing, customer loyalty, customer satisfaction, Islamic banking, mediation analysis .